2022
DOI: 10.4103/idoj.idoj_225_21
|View full text |Cite
|
Sign up to set email alerts
|

Podophyllin in dermatology: Revisiting a historical drug

Abstract: Podophyllin is a cytotoxic material extracted from Podophyllum peltatum and Podophyllum hexandrum and is widely used for the treatment of genital warts. This article reviews the chemistry of podophyllin and its active components along with the mechanism of action in various dermatoses. Furthermore, the documented uses of podophyllin in various dermatological disorders have been described along with the side effects of the drug. Based on the available literature, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…24 Genital warts are commonly treated with podophyllin, a cytotoxic substance obtained from Podophyllum peltatum and Podophyllum hexandrum. 25 Human skin keratinocytes infected with the human papillomavirus are prevented from proliferating by podophyllin, 26 which inhibits mitotic activity in rapidly dividing cells by preventing the positioning of chromosomes on the spindle during metaphase of mitosis due to a mixture of antimitotic chemicals, of which podophyllotoxin is the primary component. 27 Previous studies with podophyllin treated patients showed low clearance rates of 37%-63% and high rates of recurrence (42%-60%).…”
Section: Discussionmentioning
confidence: 99%
“…24 Genital warts are commonly treated with podophyllin, a cytotoxic substance obtained from Podophyllum peltatum and Podophyllum hexandrum. 25 Human skin keratinocytes infected with the human papillomavirus are prevented from proliferating by podophyllin, 26 which inhibits mitotic activity in rapidly dividing cells by preventing the positioning of chromosomes on the spindle during metaphase of mitosis due to a mixture of antimitotic chemicals, of which podophyllotoxin is the primary component. 27 Previous studies with podophyllin treated patients showed low clearance rates of 37%-63% and high rates of recurrence (42%-60%).…”
Section: Discussionmentioning
confidence: 99%
“…Podophyllin is a plant compound that causes cells to arrest in mitosis, leading to tissue necrosis. Podophyllum resin 10% to 25% in compound tincture of benzoin used to be the standard provider-administered therapy for genital warts [33].…”
Section: Preparation Of the Drug And The Placebomentioning
confidence: 99%
“…[12][13][14][15] Derived from the roots of the Mayapple plant (Podophyllum peltatum), podophyllum resin has historically been used in traditional medicine and is most commonly used in topical treatments for various skin conditions such as genital warts. 16,17 Podophyllum resin contains podophyllotoxin compounds with antiviral properties capable of inhibiting the growth of specific cells. 16 In the context of HIV/AIDS-related OHL, management not only focuses on addressing the underlying viral infection but also on optimizing immune function through antiretroviral therapy (ART).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Podophyllum resin contains podophyllotoxin compounds with antiviral properties capable of inhibiting the growth of specific cells. 16 In the context of HIV/AIDS-related OHL, management not only focuses on addressing the underlying viral infection but also on optimizing immune function through antiretroviral therapy (ART). 7 Routine identification of EBV in OHL after treatment aligns with the crucial tasks of monitoring viral activity to assess treatment effectiveness and the potential for recurrence.…”
Section: Introductionmentioning
confidence: 99%